Detachable string magnetically controlled capsule endoscopy for detecting high-risk varices in compensated advanced chronic liver disease (CHESS1801): A prospective multicenter study - Shuai Wang; Yifei Huang; Weiling Hu; Hua Mao; Mark Edward McAlindon; Yanna Liu; Li Yang; Chunqing Zhang; Ming Xu; Chaohui He; Tong Dang; Bin Wu; et al. (Elsevier, 2021)
Background: Gastroesophageal varices is a serious complication of compensated advanced chronic liver disease (cACLD). Primary prophylaxis to reduce the risk of variceal hemorrhage is recommended if high-risk varices (HRV) are detected. We performed this study to compare the accuracy, patients' satisfaction and safety of detection of HRV by detachable string magnetically controlled capsule endoscopy (DS-MCCE) with esophagogastroduodenoscopy (EGD) as the reference. Methods: We prospectively recruited participants with cACLD from 12 university hospitals (11 in China and one in the United Kingdom) between November 2018 and December 2019 (ClinicalTrials.gov, NCT03749954). All participants underwent DS-MCCE, followed by EGD within a week in a blinded fashion. Following endoscopy, and on the same day, participants were asked to fill in a satisfaction questionnaire regarding their experience. Findings: A total of 105 eligible participants were enrolled. With EGD as the reference standard, the concordance index, sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio of DS-MCCE in diagnosis of HRV were 0•90 (95% confidence interval [CI]: 0•83-0•95), 92% (95% CI: 78-98%), 88% (95% CI: 78-95%), 80% (95% CI: 70-92%), 95% (95% CI: 90-100%), 7•91 (95% CI: 4•10-15•30), and 0•09 (95% CI: 0•03-0•30), respectively. The kappa score of 0•78 (95% CI: 0•65-0•90) suggested substantial agreement between DS-MCCE and EGD. Moreover, in participants undergoing EGD without sedation, the satisfaction of DS-MCCE was significantly better than that of EGD (p < 0•0001, d = 1•15 [95%CI: 0•88-1•42]). All participants confirmed the excretion of the capsule, and no adverse events occurred. Interpretation: DS-MCCE is an accurate alternative to EGD for detecting HRV in cACLD, which is safe and associated with better satisfaction. Funding: A full list of funding can be found in the Funding Support section.